Projektowanie pomocy edukacyjnych: transformacyjna wartość procesu. Narracje nauczycielek i nauczycieli o własnym uczeniu się podczas stacjonarnych i zdalnych Letnich Szkół Prototypowania - Iłowiecka-Tańska, Ilona; Gop, Aneta; Jaskulska, Sylwia (Studia Edukacyjne, 2021)
The article discusses the transformative value of the process of prototyping teaching aids during a fiveday workshop for teachers. Based on sequential narrative data collected by using the diaries method, we analyze changes in individual aspects of learning in a group of teachers, the dynamics of these changes, and differences resulting from the form of classes (in-person vs online). At the end of the article, we present practical conclusions that can be implemented in educational projects dedicated to teachers.